PENGARUH GAME ONLINE VRCHAT TERHADAP KEMAMPUAN CHOUKAI PADA MAHASISWA ANGKATAN 2020 PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Nur Ainun Habibah Nasution; Merri Silvia Basri; Adisthi Martha Yohani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The purpose of this study is to examine the differences in understanding learning outcomes between students who use the VRchat game and students who do not use the VRchat game on the basic level 2 A-2 Marugoto material on topic 1 atarashii tomodachi. The research method used is a quasi-experimental method of Nonequivalent Control Group Design. This study involved 2 classes, namely the experimental class and the control class. The experimental class was given treatment using the VRchat game, while the control class only received material. Each was given a pretest and posttest. The results of data processing showed the calculation of the posttest average value of the experimental class was 64.64 while the control class was 44.28. The conclusion of the research is that there are differences in understanding learning outcomes between groups that use VRchat games and groups that do not use VRchat games. The learning outcomes of students' understanding using VRchat games were higher than the group that did not use learning games.Key Words: VRchat, Online Game, Japanese Language, Choukai, Influence